(a+b+c) (a+b-c) solve this plz vry vry imp
Answers
Answered by
1
Answer: HOPE IT HELPS
Step-by-step explanation: (vili) (a+ b + c)(atb-c)
(atb + c)(a+b-c)
= a(a + b - c) + b(a + b - c) + c(a+ b-c)
= (axa) + (axb) - (axc) + (bxa) +(bxb) - (bxc)
+ (cx a)+(cxb) -(cxc)
= a2 + ab - ac + ba + b2 - bc + ca + cb-c2
= a2 + ab - ac + ab + b2 - bc + ac + bc-c2
= a2 + b2 - c2 + ab + ab - bc + bc- ac + ac
= a2+62 - c2 + 2ab
Answered by
5
Here is your answer
Please mark me as a brainlist
Bye!
Please mark me as a brainlist
Bye!
Attachments:
![](https://hi-static.z-dn.net/files/d7e/82171b7a3bf94e3de4cc5618a3d360e1.png)
Similar questions